2008
DOI: 10.1128/ec.00362-07
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinases Involved in Mating and Osmotic Stress in the Yeast Kluyveromyces lactis

Abstract: Systematic disruption of genes encoding kinases and mitogen-activated protein kinases (MAPKs) was performed in Kluyveromyces lactis haploid cells. The mutated strains were assayed by their capacity to mate and to respond to hyperosmotic stress. The K. lactis Ste11p (KlSte11p) MAPK kinase kinase (MAPKKK) was found to act in both mating and osmoresponse pathways while the scaffold KlSte5p and the MAPK KlFus3p appeared to be specific for mating. The p21-activated kinase KlSte20p and the kinase KlSte50p participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 37 publications
4
24
0
Order By: Relevance
“…However, we observed that when KlSte11p or its adaptor protein, KlSte50p, was inactivated, growth was severely affected. All the observed phenotypes are in agreement with those described previously (25), except for that of the ⌬Klste20 mutant. We attribute this discrepancy to the different genetic background in which mutants in this study were constructed.…”
Section: Mutants With Deletions Of Components Of the Sho1 And Sln1supporting
confidence: 81%
See 4 more Smart Citations
“…However, we observed that when KlSte11p or its adaptor protein, KlSte50p, was inactivated, growth was severely affected. All the observed phenotypes are in agreement with those described previously (25), except for that of the ⌬Klste20 mutant. We attribute this discrepancy to the different genetic background in which mutants in this study were constructed.…”
Section: Mutants With Deletions Of Components Of the Sho1 And Sln1supporting
confidence: 81%
“…We included in this analysis the genes that code for the transmembrane protein KlSho1p, the PAK KlSte20p, the MAPKKK KlSte11p, and its adaptor protein, KlSte50p. For comparison, we also included ⌬Klpbs2 and ⌬Klhog1 mutants, which have been shown to be sensitive to high osmotic stress (25). As can be seen in Fig.…”
Section: Mutants With Deletions Of Components Of the Sho1 And Sln1mentioning
confidence: 99%
See 3 more Smart Citations